2002
DOI: 10.1021/jp021054t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness Extension Mode Resonance Oscillation of Acoustic Waves on Catalytic and Surface Properties. II. Ethanol Decomposition on a Thin Pd Film Catalyst Deposited on Positively Polarized z-Cut LiNbO3

Abstract: The effects of thickness extension mode resonance oscillation (TERO) of acoustic waves on the catalytic properties of a 100 nm thick Pd film deposited a positively polarized ferroelectric z-cut LiNbO 3 single crystal were studied. For ethylene and acetaldehyde production in ethanol decomposition, the TERO accelerated ethylene production only and enhanced the selectivity for ethylene production from 40% to 96%. Randomly distributed standing waves due to large lattice displacement vertical to the surface were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In previous studies, the positive work function shifts were found to increase with increasing rf power, [13][14][15] which indicated that large vertical lattice displacement was responsible for large work function shifts. Because large vertical lattice displacement occurred at low resonance frequency, compared to high frequency, it is apparent that the low frequency was able to cause large positive work function shifts, and hence the TERO effects became larger in low frequency than in high frequency.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In previous studies, the positive work function shifts were found to increase with increasing rf power, [13][14][15] which indicated that large vertical lattice displacement was responsible for large work function shifts. Because large vertical lattice displacement occurred at low resonance frequency, compared to high frequency, it is apparent that the low frequency was able to cause large positive work function shifts, and hence the TERO effects became larger in low frequency than in high frequency.…”
Section: Discussionmentioning
confidence: 86%
“…[13][14][15] Based on the findings, a mechanism for TERO effects on work function was proposed. The work function of a transition metal is mainly determined by the barrier of an electric double layer that is formed by electrons spilled out from the topmost layer of a metal surface and positive charges remaining in the interior of the bulk metal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations